Serospecific antigens of Legionella pneumophila. - Otten, S (1986)
Serospecific antigens isolated by EDTA extraction from four serogroups of Legionella pneumophila were analyzed for their chemical composition, molecular heterogeneity by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, and immunological properties. The antigens were shown to be lipopolysaccharides and to differ from the lipopolysaccharides of other gram-negative bacteria. The serospecific antigens contained rhamnose, mannose, glucosamine, and two unidentified sugars together with 2-keto-3-deoxyoctonate, phosphate, and fatty acids. The fatty acid composition was predominantly branched-chain acids with smaller amounts of 3-hydroxymyristic acid. The antigens contain periodate-sensitive groups; mannosyl residues were completely cleaved by periodate oxidation. Hydrolysis of the total lipopolysaccharide by acetic acid resulted in the separation of a lipid A-like material that cross-reacted with the antiserum to lipid A from Salmonella minnesota but did not comigrate with it on sodium dodecyl sulfate gels. None of the four antigens contained heptose. All of the antigen preparations showed endotoxicity when tested by the Limulus amebocyte lysate assay. The results of this study indicate that the serogroup-specific antigens of L. pneumophila are lipopolysaccharides containing an unusual lipid A and core structure and different from those of other gram-negative bacteria.